Environment-friendly sunlight-resistant microcapsule, environment-friendly sunlight-resistant asphalt additive and preparation method thereof
By using environmentally friendly and sun-resistant microcapsules in asphalt and using the combination of composite shell material and phase change core material, the ultraviolet aging, thermal aging and environmental pollution caused by sunlight are solved, and a longer service life and better environmental friendliness are achieved.
Patent Information
- Application Number
- CN202311358662.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
The existing technology cannot effectively solve the problems of ultraviolet aging, thermal aging and environmental pollution caused by sunlight on asphalt pavement. The existing additives have poor compatibility and poor stability, and cannot solve the problems of high temperature and ultraviolet aging on the pavement at the same time.
The environmentally friendly and sun-resistant microcapsules are used to achieve temperature control, anti-UV aging and in-situ capture effects through the combination of composite shell materials and phase change core materials, reducing the diseases affected by high temperature and ultraviolet rays on asphalt pavement.
Effectively extend the service time of asphalt pavement, reduce the irritating gas released on the pavement, reduce the degree of ultraviolet aging, and improve the overall performance and environmental friendliness of asphalt pavement.
Smart Images

Figure CN119859322A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of special asphalt, and specifically relates to an environmentally friendly sunlight-resistant microcapsule, an environmentally friendly sunlight-resistant asphalt additive and a preparation method thereof. Background Art
[0002] Nowadays, with the rapid development of municipal transportation, asphalt roads are also expanding as the main form of traffic pavement. Asphalt pavement has many advantages, such as low noise, high flatness, and easy construction. However, in sunny areas, long-term sunlight exposure will cause ultraviolet aging of asphalt pavement, making it hard and brittle and easy to break; on the other hand, it will increase the temperature of the pavement, which will cause the asphalt to soften, and then cause problems such as lumps, oiling, and cracking, which will affect the service life of the asphalt pavement. At the same time, it will also cause the small molecular compounds in the asphalt system to volatilize due to heat, which will not only make the asphalt further age and become brittle, but also react with automobile exhaust gas under sunlight to generate photochemical smog, which will harm the ecological environment and affect human health.
[0003] CN101434472A discloses a method for improving the anti-ultraviolet aging performance of modified asphalt. The method delays the degree of asphalt being affected by ultraviolet aging by adding nanomaterials and ultraviolet absorbers with ultraviolet absorption function to asphalt. Such additives have poor compatibility with asphalt and will affect the road performance of asphalt after being added to asphalt. At the same time, the stability of such additives is also poor, and a large amount of them will be lost during the high-temperature mixing process and the subsequent heat absorption and temperature rise process of the road surface, which seriously affects its anti-ultraviolet performance. In addition, such additives cannot solve a series of problems caused by high temperature of the road surface due to sunlight exposure.
[0004] CN111303646A discloses a modified asphalt that realizes self-temperature adjustment based on phase change microcapsules. The modified asphalt reduces the road surface temperature by virtue of the phase change heat absorption property of the core material of the phase change material microcapsule, thereby extending the service life of the road surface. However, the shell material of this type of microcapsule is relatively low in strength, and the microcapsules are easily broken during the asphalt mixing process, which weakens its road surface cooling performance. In addition, this type of microcapsule cannot solve a series of problems caused by UV aging of the road surface.
[0005] In summary, the existing technology does not completely solve the series of problems caused by the influence of sunlight on the asphalt pavement of petroleum roads. The asphalt materials prepared by simply adding light stabilizers or phase change materials to asphalt using the above method have poor resistance to ultraviolet aging, heat aging and compatibility with asphalt. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides an environmentally friendly sunlight-resistant microcapsule, an environmentally friendly sunlight-resistant asphalt additive and a preparation method thereof. Through the temperature control, anti-ultraviolet aging and in-situ capture effects of the environmentally friendly sunlight-resistant microcapsules, the diseases caused by high temperature and ultraviolet light on asphalt are reduced, the service life of asphalt pavement is effectively increased, and the amount of small molecule compounds released by asphalt pavement under the influence of high temperature is reduced, thereby solving the environmental problems existing in asphalt pavement.
[0007] The first aspect of the present invention provides an environmentally friendly sunlight-resistant microcapsule, which includes a shell material and a core material. The shell material is a composite shell material including titanium dioxide / nano-tourmaline / polydopamine, the core material is a normal alkane with a phase change temperature of 40°C-60°C, and the surface of the shell material is loaded with metal chelates and light stabilizers.
[0008] Furthermore, the light stabilizer is selected from one or more of a benzophenone light stabilizer having more than 10 carbon atoms or a hindered amine light stabilizer having more than 15 carbon atoms.
[0009] Furthermore, the benzophenone-based light stabilizer having a carbon number greater than 10 is selected from one or more of BP-1 (2,4-dihydroxybenzophenone), BP-2 (2,2',4,4'-tetrahydroxybenzophenone), BP-3 (4-methoxy-2-hydroxybenzophenone), BP-4 (2-hydroxy-4-methoxy-5-sulfonic acid benzophenone), BP-8 (2,2'-hydroxy-4-methoxybenzophenone), and BP-12 (2-hydroxy-4-n-octyloxybenzophenone).
[0010] Furthermore, the hindered amine light stabilizer having a carbon number greater than 15 is selected from HALS-770 (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate), HALS-292 (bis(1,2,2,6,6-pentamethylpiperidinol) sebacate), HALS-3346 (poly[(6-morpholinyl-1,3,5-triazine-2,4-yl)-((2,2,6,6-tetramethyl-4-piperidinyl)imino)hexane-((2,2,6,6-tetramethyl -4-piperidinyl)imino)]), HALS-944 (poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]), HALS-112 (bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl)sebacate).
[0011] Furthermore, the particle size of the environmentally friendly sunlight-resistant microcapsules is 1-5 μm.
[0012] Furthermore, the mass ratio of the shell material to the core material of the environmentally friendly sunlight-resistant microcapsule is 1:(0.5-2).
[0013] Furthermore, the shell material of the environmentally friendly sunlight-resistant microcapsule is a composite shell material including titanium dioxide / nano-tourmaline / polydopamine, wherein the mass ratio of titanium dioxide to nano-tourmaline is (1-5):1, and the mass ratio of titanium dioxide to polydopamine shell material is 1:(0.1-0.5).
[0014] Furthermore, the surface of the shell material is loaded with a metal chelate, wherein the metal is preferably copper.
[0015] Furthermore, the shell material surface is loaded with metal chelate, the metal loading accounts for 0.1wt%-15wt% of the total mass of the environmentally friendly sunlight-resistant microcapsule; the light stabilizer loading accounts for 0.1wt%-20wt% of the total mass of the environmentally friendly sunlight-resistant microcapsule.
[0016] Furthermore, the normal alkane with a phase transition temperature of 40°C-60°C is preferably one or more of n-octadecane, n-eicosane and n-docosane.
[0017] The second aspect of the present invention provides a method for preparing environmentally friendly sunlight-resistant microcapsules, comprising the following steps:
[0018] S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the mixture under stirring, washing the mixture after the modification, and freeze-drying the mixture to obtain modified nano-tourmaline;
[0019] S2: heating the core material for later use;
[0020] S3: adding the solvent and the modified nano-tourmaline obtained in step S1 to the system in step S2, and stirring and mixing;
[0021] S4: adding a titanium dioxide precursor to the reaction system in step S3, stirring and mixing, and obtaining a Pickering emulsion;
[0022] S5: adjusting the pH value of the Pickering emulsion obtained in step S4 to 2-5, continuing stirring, then aging, filtering, and freeze-drying;
[0023] S6: adding the solid powder obtained in step S5 to a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying;
[0024] S7: adding the solid powder and the light stabilizer obtained in step S6 to an organic solvent, adding a strong base and reacting under heating reflux conditions, cooling, filtering, washing, and freeze-drying;
[0025] S8: adding the solid powder obtained in step S7 to the metal salt ion-formamide solution, treating under stirring, filtering, washing, and freeze-drying after the reaction is completed, so as to obtain environmentally friendly sunlight-resistant microcapsules.
[0026] Furthermore, in step S1, the diameter of the nano-tourmaline is 10-100 nm.
[0027] Furthermore, the surfactant in step S1 is a cationic surfactant, preferably one or more of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride.
[0028] Furthermore, in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.
[0029] Furthermore, in step S1, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (5-60):1.
[0030] Furthermore, in step S1, the stirring speed is 400-600 rpm; the modification temperature is 100-200° C., and the modification time is 4-10 hours.
[0031] Furthermore, in step S1, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0032] Furthermore, in step S2, the core material is heated to a temperature of 40-60°C.
[0033] Furthermore, in step S3, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.
[0034] Furthermore, in step S3, the mass ratio of the core material raw material to the modified nano-tourmaline is (1-20): 1. The mass ratio of the solvent to the modified nano-tourmaline is (10-80): 1.
[0035] Furthermore, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.
[0036] Furthermore, in step S4, the titanium dioxide precursor is one or more of n-butyl titanate, tetra-n-propyl titanate, and tetraethyl titanate.
[0037] Furthermore, in step S4, the mass ratio of the core material raw material to the titanium dioxide precursor is 1:(0.5-2).
[0038] Furthermore, in step S4, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.
[0039] Furthermore, in step S5, the pH value can be adjusted by using dilute acid, such as dilute hydrochloric acid. The stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.
[0040] Furthermore, in step S5, the aging condition is: standing at 40-60°C for 12-30 hours. The freeze-drying condition is: vacuum drying at a temperature of -40--20°C for 4-8 hours.
[0041] Furthermore, in step S6, the buffer is one or more of phosphate buffer, carbonate buffer, and Tris buffer, preferably Tris buffer.
[0042] Furthermore, in step S6, the pH value of the buffer solution is 8-10.
[0043] Furthermore, in step S6, the mass ratio of the buffer solution to the solid powder obtained in step S5 is (30-200):1.
[0044] Furthermore, in step S6, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.
[0045] Furthermore, in step S6, the stirring speed is 100-300 rpm, the stirring temperature is 20-30° C., and the stirring time is 12-24 hours.
[0046] Furthermore, in step S6, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0047] Furthermore, in step S7, the strong base is one of solid KOH and solid NaOH, preferably solid KOH.
[0048] Furthermore, the organic solvent in step S7 is selected from one or more of methanol, butanediol, ethylene glycol, n-butanol, and anhydrous ethanol.
[0049] Furthermore, in step S7, the reaction temperature is 80-240° C., and the reaction time is 5-10 hours.
[0050] Furthermore, in step S7, the mass ratio of the solid powder to the organic solvent is 1:(20-100), the mass ratio of the solid powder to the light stabilizer is 1:(20-80), and the mass ratio of the solid powder to the strong base is 1:(0.5-4).
[0051] Furthermore, in step S7, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0052] Further, in step S8, the metal ion salt is preferably a copper ion salt, and more preferably anhydrous copper sulfate.
[0053] Furthermore, in step S8, in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1.
[0054] Furthermore, in step S8, the mass ratio of the metal ion salt-formamide solution to the solid powder obtained in step S7 is (10-100):1.
[0055] Furthermore, the stirring speed is 200-450 rpm, the stirring temperature is 100-190° C., and the stirring time is 2-5 hours.
[0056] Furthermore, in step S8, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0057] The third aspect of the present invention provides an environmentally friendly sunlight-resistant asphalt additive, which comprises the following components by weight:
[0058] 1-5 parts of the above environmentally friendly sunlight-resistant microcapsules;
[0059] Dispersant, 1-10 parts.
[0060] Furthermore, the dispersant is one or more of dodecyl dimethyl betaine and 1-hydroxyethyl-carboxymethyl-alkyl imidazoline.
[0061] Furthermore, the environmentally friendly sunlight-resistant microcapsules are added to the dispersant, and mixed for 2-4 hours at a temperature of 25-45° C. and a stirring speed of 200-400 rpm to obtain an environmentally friendly sunlight-resistant asphalt additive.
[0062] A fourth aspect of the present invention provides an environmentally friendly sunlight-resistant asphalt, comprising the following components by weight:
[0063] Base asphalt, 100-300 parts;
[0064] The above-mentioned environmentally friendly sunlight-resistant asphalt additive, 1-30 parts.
[0065] Furthermore, the base asphalt is commercially available No. 50, No. 70 and No. 90 road asphalt, preferably No. 70 Grade A asphalt.
[0066] Furthermore, under a nitrogen atmosphere and at a temperature of 133-173°C, the base asphalt is heated to a molten state, an environmentally friendly sunlight-resistant asphalt additive is added to the asphalt, and the mixture is mixed at a stirring speed of 800-1000 rpm for 50-300 minutes to obtain the environmentally friendly sunlight-resistant asphalt.
[0067] Compared with the prior art, the present invention has the following advantages:
[0068] (1) The environmentally friendly sunlight-resistant microcapsules of the present invention have three functions in their composite shell material. The first function is that during the preparation process, nano-tourmaline serves as a template for the synthesis of microcapsules, which can maintain the stability of the precursor emulsion; the second function is that during the metal ion modification of the microcapsule composite shell material, a large amount of metal ions can be adsorbed onto the surface of the microcapsules with the help of the negative ion field released by tourmaline, effectively increasing the metal ion loading capacity of the microcapsule shell material, and further improving the smoke suppression ability of the environmentally friendly sunlight-resistant microcapsules; the third function is that during the service process of the road surface, after the environmentally friendly sunlight-resistant microcapsules are heated, the nano-tourmaline contained in the shell material will release a negative ion field, further attracting the compounds released by the asphalt pavement under the action of high temperature to the vicinity of the environmentally friendly sunlight-resistant microcapsules, while increasing the difficulty of these compounds to volatilize, the metal ions on the surface of the microcapsules can react with more of the above-mentioned compounds, further inhibiting their volatilization, thereby effectively reducing the impact of the irritating gases released by the asphalt pavement on the human body.
[0069] (2) The environmentally friendly sunlight-resistant microcapsules of the present invention, wherein the titanium dioxide shell material can shield ultraviolet rays; the surface of the polydopamine shell material has a large number of active groups such as quinone groups and phenolic hydroxyl groups, and has good anti-ultraviolet ability. With the help of the large number of active groups on the surface of the polydopamine shell layer, the light stabilizer is immobilized on the surface of the microcapsule through Schiff base reaction and Michael addition reaction. After immobilization, the stability of the light stabilizer is greatly improved, and the loss of the light stabilizer caused by heat is effectively avoided, and it has a long-lasting and efficient anti-ultraviolet ability. After adding asphalt, the composite layer shell material of the environmentally friendly sunlight-resistant microcapsules can synergistically exert good anti-ultraviolet ability, effectively reducing the degree of ultraviolet aging during the service of asphalt pavement.
[0070] (3) The environmentally friendly sunlight-resistant microcapsules of the present invention have metal ions on the surface of the composite shell material that can chemically react with small molecular compounds released by asphalt pavement under high temperature, effectively reducing the malodorous gases released by asphalt under high temperature and sunlight, thereby preventing asphalt pavement from causing discomfort to the human body.
[0071] (4) The environmentally friendly sunlight-resistant microcapsule core material of the present invention can undergo phase change to absorb heat when the temperature of asphalt rises, effectively reducing the temperature of the asphalt pavement. It can not only reduce the amount of small molecule gas compounds released by the asphalt pavement, but also effectively reduce the diseases of the asphalt pavement caused by high temperature and extend the service life of the asphalt pavement.
[0072] (5) The environmentally friendly sunlight-resistant microcapsules of the present invention have an organic-inorganic multilayer composite shell material, which has high strength, is not easy to break, and has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is an electron microscope image of the environmentally friendly sunlight-resistant microcapsules obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0074] To further illustrate the technical solution of the present invention, the present invention will be clearly and detailed described below in conjunction with embodiments.
[0075] The present invention uses a ZEISS Supra55 scanning electron microscope to perform morphology testing, and the acceleration voltage used is 20 kV. Since the microcapsule wall material is not conductive, the sample needs to be treated with gold spraying before testing;
[0076] The environmentally friendly sunlight-resistant microcapsules of the present invention are tested for surface elements by a Bruker XFlash 6160 X-ray spectrometer to confirm that the metal ions are successfully modified on the surface of the microcapsules;
[0077] The flue gas generated during the use of the environmentally friendly sunlight-resistant asphalt of the present invention is tested by meteorological chromatography, and the test items are non-methane total hydrocarbons and sulfides.
[0078] The base asphalt used in the following examples and comparative examples is Sinopec Donghai brand No. 70 Grade A asphalt.
[0079] Example 1
[0080] S1: Add tourmaline with a diameter of 70 nm, hexadecyltrimethylammonium bromide and formamide in a mass ratio of 2:1:40 into a first container, stir and react at 500 rpm and 190°C for 6 hours to modify the surface of the nano tourmaline, wash with ethanol several times after the reaction is completed, and vacuum dry at -30°C for 5 hours to obtain modified nano tourmaline for standby use;
[0081] S2: Add 5 parts by mass of n-docosane into the second container, and heat it at 50° C. until it is melted for later use;
[0082] S3: Add 50°C formamide and the modified nano-tourmaline obtained in step S1 to the above system, and stir at 50°C and 500 rpm for 5 hours, wherein the mass ratio of n-docosane, modified nano-tourmaline and formamide is 5:2:50;
[0083] S4: adding 5 parts by mass of n-butyl titanate to the system of step S3, maintaining the rotation speed of 500 rpm and the temperature of 50° C., and continuing stirring for 4 hours to obtain a Pickering emulsion;
[0084] S5: Keeping the rotation speed at 500 rpm and the temperature at 50°C unchanged, use a peristaltic pump to slowly add 10 wt% dilute hydrochloric acid to the system of S4 until the pH of the reaction system is 5, continue stirring for 5 hours and then stop stirring, keep the temperature unchanged and age for 24 hours, then filter and wash the solid powder in the reaction system, and vacuum dry it at -30°C for 5 hours to obtain an environmentally friendly sunlight-resistant microcapsule precursor;
[0085] S6: 10 parts by weight of the environmentally friendly sunlight-resistant microcapsule precursor is added to 100 parts by weight of a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the solid powder is 80:1, and then dopamine hydrochloride is added to make the concentration of dopamine in the reaction system 3 mg / mL, and the mixture is stirred at 200 rpm for 12 hours at 25°C, and then the stirring is stopped. The bottom solid powder is filtered and washed, and then vacuum dried at a temperature of -30°C for 5 hours;
[0086] S7: adding the solid powder obtained in step S6 and the light stabilizers BP-1, BP-4 and HALS-770 in equal mass ratio to anhydrous ethanol, further adding solid KOH, wherein the mass ratio of the solid powder obtained in step S6, the light stabilizer, anhydrous ethanol and solid KOH is 1:60:60:3, and refluxing the reaction at 85°C for 10 hours, then filtering and washing the bottom solid powder, and vacuum drying the mixture at -30°C for 5 hours;
[0087] S8: Ultrasonic dispersion of the solid powder obtained in step S7 in a 50wt% anhydrous copper sulfate-formamide solution, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution being 1:60, stirring and reacting at 400 rpm and 140°C for 2 hours, filtering and washing the bottom solid powder after the reaction, and vacuum drying at -30°C for 5 hours to obtain environmentally friendly sunlight-resistant microcapsules, the electron microscope image of which is shown in FIG. Figure 1 .
[0088] The environmentally friendly sunlight-resistant asphalt additive can be prepared by mixing 3 parts by mass of dodecyl dimethyl betaine with 2 parts by mass of environmentally friendly sunlight-resistant microcapsules at a temperature of 25° C. and a stirring speed of 200 rpm for 2 hours.
[0089] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. While keeping the gas and temperature conditions unchanged, 5 parts by mass of an environmentally friendly, sun-resistant asphalt additive were added to the asphalt. The mixture was stirred and mixed at a speed of 800 rpm for 100 minutes to obtain the environmentally friendly, sun-resistant asphalt.
[0090] Example 2
[0091] Except that in step S7, the light stabilizers are BP-2, BP-8, and HALS-944 in equal weight ratios, the rest is the same as in Example 1.
[0092] Example 3
[0093] Except for step S7, the mass ratio of the solid powder obtained in step S6, the light stabilizer, anhydrous ethanol and KOH is 1:50:60:3, and the rest is the same as that of embodiment 1.
[0094] Example 4
[0095] Except that when preparing the environmentally friendly sunlight-resistant asphalt additive, the dispersant is 1-hydroxyethyl-carboxymethyl-alkyl imidazoline, the rest is the same as Example 1.
[0096] Example 5
[0097] When preparing the environmentally friendly sunlight-resistant asphalt additive, the amount of dodecyl dimethyl betaine added is 4 parts by mass, and the amount of environmentally friendly sunlight-resistant microcapsules added is 1 part by mass, and the rest is the same as Example 1.
[0098] Example 6
[0099] When preparing the environmentally friendly sunlight-resistant asphalt additive, the amount of dodecyl dimethyl betaine added is 2 parts by mass, and the amount of environmentally friendly sunlight-resistant microcapsules added is 3 parts by mass, and the rest is the same as Example 1.
[0100] Example 7
[0101] Except that in step S3, the mass ratio of n-docosane, modified nano-tourmaline and formamide is 5:1:50, the rest is the same as that in Example 1.
[0102] Example 8
[0103] Except that in step S8, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:50, the rest is the same as that of Example 1.
[0104] Comparative Example 1
[0105] Steps S1-S5 are the same as in Embodiment 1, and steps S6-S8 are omitted.
[0106] The environmentally friendly sunlight-resistant asphalt additive can be obtained by mixing 3 parts by mass of dodecyl dimethyl betaine with 2 parts by mass of the environmentally friendly sunlight-resistant microcapsule precursor prepared in step S5 at a temperature of 25° C. and a stirring speed of 200 rpm for 2 hours.
[0107] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. While keeping the gas and temperature conditions unchanged, 5 parts by mass of an environmentally friendly, sun-resistant asphalt additive were added to the asphalt. The mixture was stirred and mixed at a speed of 800 rpm for 100 minutes to obtain the environmentally friendly, sun-resistant asphalt.
[0108] Comparative Example 2
[0109] Steps S1-S6 are the same as in Example 1;
[0110] S7: Ultrasonic dispersion of the solid powder obtained in step S6 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:60, and the reaction is stirred at 400 rpm and 140°C for 2 hours. After the reaction is completed, the bottom solid powder is filtered and washed, and vacuum dried at -30°C for 5 hours to obtain environmentally friendly sunlight-resistant microcapsules.
[0111] The environmentally friendly sunlight-resistant asphalt additive can be prepared by mixing 3 parts by mass of dodecyl dimethyl betaine with 2 parts by mass of environmentally friendly sunlight-resistant microcapsules at a temperature of 25° C. and a stirring speed of 200 rpm for 2 hours.
[0112] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. While keeping the gas and temperature conditions unchanged, 5 parts by mass of an environmentally friendly, sun-resistant asphalt additive were added to the asphalt. The mixture was stirred and mixed at a speed of 800 rpm for 100 minutes to obtain the environmentally friendly, sun-resistant asphalt.
[0113] Comparative Example 3
[0114] Steps S1-S7 are the same as in Example 1, and step S8 is omitted;
[0115] An environmentally friendly sunlight-resistant asphalt additive can be obtained by mixing 3 parts by mass of dodecyl dimethyl betaine with 2 parts by mass of the solid powder obtained in step S7 at a temperature of 25° C. and a stirring speed of 200 rpm for 2 hours.
[0116] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. While keeping the gas and temperature conditions unchanged, 5 parts by mass of an environmentally friendly, sun-resistant asphalt additive were added to the asphalt. The mixture was stirred and mixed at a speed of 800 rpm for 100 minutes to obtain the environmentally friendly, sun-resistant asphalt.
[0117] Comparative Example 4
[0118] The preparation of environmentally friendly sunlight-resistant microcapsules is the same as in Example 1.
[0119] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. Further, while keeping the gas and temperature conditions unchanged, 2 parts by mass of environmentally friendly sun-resistant microcapsules were added to the asphalt. After stirring and mixing at a speed of 800 rpm for 100 minutes, environmentally friendly sun-resistant asphalt was obtained.
[0120] Comparative Example 5
[0121] S1: Add 5 parts by mass of n-docosane into a container and heat it at 50°C until it melts for later use;
[0122] S2: Add 50°C formamide and hexadecyltrimethylammonium bromide to the above system, stir at 50°C and 500 rpm for 5 hours, the mass ratio of n-docosane, hexadecyltrimethylammonium bromide and formamide is 5:2:50;
[0123] S3: adding 5 parts by mass of n-butyl titanate to the system of step S2, maintaining the rotation speed of 500 rpm and the temperature of 50° C., and continuing stirring for 4 hours to obtain a Pickering emulsion;
[0124] S4: keeping the rotation speed at 500 rpm and the temperature at 50°C unchanged, using a peristaltic pump to slowly add 10 wt% dilute hydrochloric acid to the system in step S3 until the pH of the reaction system is 5, and then stopping stirring after continuing stirring for 5 hours, keeping the temperature unchanged and aging for 24 hours, then filtering and washing the solid powder in the reaction system, and vacuum drying at -30°C for 5 hours to obtain an environmentally friendly sunlight-resistant microcapsule precursor;
[0125] S5: 10 parts by weight of the environmentally friendly sunlight-resistant microcapsule precursor is added to 100 parts by weight of a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the solid powder is 80:1, and then dopamine hydrochloride is added to make the concentration of dopamine in the reaction system 3 mg / mL. The mixture is stirred at 200 rpm for 12 hours at 25°C, and then the stirring is stopped. The bottom solid powder is filtered and washed, and then vacuum dried at -30°C for 5 hours.
[0126] S6: adding the solid powder obtained in step S5 and the light stabilizers BP-1, BP-4 and HALS-770 in equal mass ratio to anhydrous ethanol, further adding solid KOH, wherein the mass ratio of the solid powder obtained in step S5, the light stabilizer, anhydrous ethanol and solid KOH is 1:60:60:3, and refluxing the reaction at 85° C. for 10 hours, then filtering and washing the bottom solid powder, and vacuum drying the mixture at -30° C. for 5 hours;
[0127] S7: Ultrasonic dispersion of the solid powder obtained in step S6 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:60, and the reaction is stirred at 400 rpm and 140°C for 2 hours. After the reaction is completed, the bottom solid powder is filtered and washed, and vacuum dried at -30°C for 5 hours to obtain environmentally friendly sunlight-resistant microcapsules.
[0128] The environmentally friendly sunlight-resistant asphalt additive can be prepared by mixing 3 parts by mass of dodecyl dimethyl betaine with 2 parts by mass of environmentally friendly sunlight-resistant microcapsules at a temperature of 25° C. and a stirring speed of 200 rpm for 2 hours.
[0129] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. While keeping the gas and temperature conditions unchanged, 5 parts by mass of an environmentally friendly, sun-resistant asphalt additive were added to the asphalt. The mixture was stirred and mixed at a speed of 800 rpm for 100 minutes to obtain the environmentally friendly, sun-resistant asphalt.
[0130] Comparative Example 6
[0131] Under a nitrogen atmosphere and a temperature of 155°C, 100 parts by mass of base asphalt were heated to a molten state. Further, while keeping the gas and temperature conditions unchanged, 3 parts by mass of dodecyl dimethyl betaine were added to the asphalt. After stirring and mixing at a speed of 800 rpm for 100 minutes, an environmentally friendly, sun-resistant asphalt was obtained.
[0132] Test Example 1
[0133] The UV aging test was carried out in a UV aging box with an UV intensity of 1200 μW / cm 2 The aging temperature is 60°C and the aging time is 10 days. After the aging is completed, the conventional asphalt performance analysis is performed on the environmentally friendly sunlight-resistant asphalt obtained. The obtained data is shown in Table 1 below.
[0134] Table 1 Asphalt performance test and storage stability test data
[0135] Test samples Softening point / ℃ Needle penetration / 0.1mm Elongation 10℃ / cm Example 1 47.8 73 37.6 Example 2 47.9 73 37.7 Example 3 49.8 70 36.1 Example 4 47.9 74 37.7 Example 5 51.3 68 35.1 Example 6 50.2 69 35.8 Example 7 49.2 71 36.5 Example 8 48.7 72 36.9 Comparative Example 1 56.4 62 31.9 Comparative Example 2 54.0 65 33.3 Comparative Example 3 52.1 67 34.5 Comparative Example 4 55.0 63 32.7 Comparative Example 5 53.1 66 33.9 Comparative Example 6 57.4 61 30.6
[0136] Test Example 2
[0137] The environmentally friendly sunlight-resistant asphalt samples obtained in the embodiment and the comparative example were respectively prepared into rectangular samples of 10cm*10cm*3cm, and the samples were moved into a sealed container with a gas intake port and stored at a temperature of 100°C for 1 day. After the storage was completed, the gas in the sealed container was absorbed, and the non-methane total hydrocarbons and sulfide content in the gas were tested using a gas chromatography. The obtained data are shown in Table 2 below.
[0138] Table 2 Asphalt VOCs test data
[0139]
[0140]
[0141] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An environmentally friendly sunlight-resistant microcapsule, characterized in that: The environmentally friendly sunlight-resistant microcapsule comprises a shell material and a core material. The shell material is a composite shell material comprising titanium dioxide / nano-tourmaline / polydopamine. The core material is a normal alkane with a phase transition temperature of 40°C-60°C. The surface of the shell material is loaded with metal chelates and light stabilizers.
2. The environmentally friendly sunlight-resistant microcapsule according to claim 1, characterized in that: The light stabilizer is selected from one or more of a benzophenone light stabilizer having a carbon number greater than 10 or a hindered amine light stabilizer having a carbon number greater than 15; Preferably, the benzophenone light stabilizer having a carbon number greater than 10 is selected from one or more of 2,4-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 4-methoxy-2-hydroxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone, 2,2'-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone; Preferably, the hindered amine light stabilizer having a carbon number greater than 15 is selected from bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethylpiperidinol) sebacate, poly[(6-morpholinyl-1,3,5-triazine-2,4-yl)-((2,2,6,6-tetramethyl-4-piperidinyl)imino)hexane-((2,2,6,6-tetramethyl-4-piperidinyl)imino)hexane- One or more of the group consisting of: poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]], and bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl)sebacate.
3. The environmentally friendly sunlight-resistant microcapsule according to claim 1, characterized in that: The particle size of the environmentally friendly sunlight-resistant microcapsules is 1-5 μm.
4. The environmentally friendly sunlight-resistant microcapsule according to claim 1, characterized in that: The mass ratio of the shell material to the core material of the environmentally friendly sunlight-resistant microcapsule is 1:(0.5-2); And / or, the mass ratio of titanium dioxide to nano-tourmaline is (1-5):1, and the mass ratio of titanium dioxide to polydopamine shell material is 1:(0.1-0.5).
5. The environmentally friendly sunlight-resistant microcapsule according to claim 1, characterized in that: The shell material surface is loaded with metal chelate, wherein the metal is preferably copper; the metal loading accounts for 0.1wt%-15wt% of the total mass of the environmentally friendly sunlight-resistant microcapsules; the light stabilizer loading accounts for 0.1wt%-20wt% of the total mass of the environmentally friendly sunlight-resistant microcapsules.
6. The environmentally friendly sunlight-resistant microcapsule according to claim 1, characterized in that: The normal alkane with a phase transition temperature of 40°C-60°C is one or more of n-octadecane, n-eicosane and n-docosane.
7. A method for preparing environmentally friendly sunlight-resistant microcapsules, characterized in that: The following steps are involved: S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the mixture under stirring, washing the mixture after the modification, and freeze-drying the mixture to obtain modified nano-tourmaline; S2: heating the core material for later use; S3: adding the solvent and the modified nano-tourmaline obtained in step S1 to the system in step S2, and stirring and mixing; S4: adding a titanium dioxide precursor to the reaction system in step S3, stirring and mixing, and obtaining a Pickering emulsion; S5: adjusting the pH value of the Pickering emulsion obtained in step S4 to 2-5, continuing stirring, then aging, filtering, and freeze-drying; S6: adding the solid powder obtained in step S5 to a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying; S7: adding the solid powder and the light stabilizer obtained in step S6 to an organic solvent, adding a strong base and reacting under heating reflux conditions, cooling, filtering, washing, and freeze-drying; S8: adding the solid powder obtained in step S7 to the metal salt ion-formamide solution and treating under stirring. After the reaction is completed, filtering, washing, and freeze-drying are performed to obtain environmentally friendly sunlight-resistant microcapsules.
8. The preparation method according to claim 7, characterized in that: Step S1: the surfactant is a cationic surfactant, preferably one or more of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride; the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; And / or, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (5-60):
1.
9. The preparation method according to claim 7, characterized in that: In step S1, the stirring speed is 400-600 rpm; the modification temperature is 100-200° C., and the modification time is 4-10 hours; And / or, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours; And / or, in step S4, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours; And / or, in step S5, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours; And / or, in step S6, the stirring speed is 100-300 rpm, the stirring temperature is 20-30° C., and the stirring time is 12-24 hours; And / or, in step S8, the stirring speed is 200-450 rpm, the stirring temperature is 100-190° C., and the stirring time is 2-5 hours.
10. The preparation method according to claim 7, characterized in that: In step S2, the core material is heated to a temperature of 40-60°C.
11. The preparation method according to claim 7, characterized in that: In step S3, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide.
12. The preparation method according to claim 7, characterized in that: In step S3, the mass ratio of the core material raw material to the modified nano-tourmaline is (1-20):1; the mass ratio of the solvent to the modified nano-tourmaline is (10-80):
1.
13. The preparation method according to claim 7, characterized in that: In step S4, the titanium dioxide precursor is one or more of n-butyl titanate, tetra-n-propyl titanate, and tetraethyl titanate; And / or, the mass ratio of the core material raw material to the titanium dioxide precursor is 1:(0.5-2).
14. The preparation method according to claim 7, characterized in that: In step S6, the buffer is one or more of a phosphate buffer, a carbonate buffer, and a tris(hydroxymethyl)aminomethane hydrochloride buffer, preferably a tris(hydroxymethyl)aminomethane hydrochloride buffer; And / or, the pH value of the buffer is 8-10; And / or, the mass ratio of the buffer solution to the solid powder obtained in step S5 is (30-200):
1.
15. The preparation method according to claim 7, characterized in that: In step S6, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.
16. The preparation method according to claim 7, characterized in that: In step S7, the strong base is one of solid KOH and solid NaOH, preferably solid KOH; And / or, the organic solvent is selected from one or more of methanol, butanediol, ethylene glycol, n-butanol, and anhydrous ethanol; And / or, the mass ratio of the solid powder to the organic solvent is 1:(20-100), the mass ratio of the solid powder to the light stabilizer is 1:(20-80), and the mass ratio of the solid powder to the strong base is 1:(0.5-4).
17. The preparation method according to claim 7, characterized in that: In step S7, the reaction temperature is 80-240° C., and the reaction time is 5-10 hours.
18. The preparation method according to claim 7, characterized in that: In step S8, in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1; And / or, the mass ratio of the metal ion salt-formamide solution to the solid powder obtained in step S7 is (10-100):
1.
19. An environmentally friendly sunlight-resistant asphalt additive, characterized in that: By weight Includes the following components: 1-5 parts of the environmentally friendly sunlight-resistant microcapsules according to any one of claims 1-6 or the environmentally friendly sunlight-resistant microcapsules prepared by the method according to any one of claims 7-18; Dispersant, 1-10 parts.
20. The environmentally friendly sunlight-resistant asphalt additive according to claim 19, characterized in that: The dispersant is one or more of dodecyl dimethyl betaine and 1-hydroxyethyl-carboxymethyl-alkyl imidazoline.
21. An environmentally friendly sunlight-resistant asphalt, characterized in that: The following components are included by weight: Base asphalt, 100-300 parts; 1-30 parts of the environmentally friendly sunlight-resistant asphalt additive described in any one of claims 19-20.
Citation Information
Patent Citations
Method for improving anti-ultraviolet aging characteristic of SBR modified asphalt
CN101434472A
Environment-friendly phase change heat storage modified asphalt and preparation method thereof
CN110872443A
Modified asphalt capable of realizing self-temperature adjustment based on phase change microcapsule
CN111303646A
Preparation method of self-temperature-adjusting asphalt pavement change microcapsule in large-temperature-difference region
CN115322752A
Thermal insulating coating employing microencapsulated phase change material and method
US5804297A